Melatonin receptor agonist ramelteon alleviates experimental acute ocular inflammation via HIF-1Α/VEGF/E-NOS signaling. Issue 2 (March 2023) - Usta Sofu, Gulsah; Erzurumlu, Yalcın; Karaca, Umut; Candan, Ibrahim Aydın; Savran, Mehtap; Asci, Halil; Hasseyid, Nursel
Purpose: Ramelteon (RML) is a potent, selective agonist of the high-affinity melatonin receptor 1 and 2 receptors. In addition, RML is known to have antioxidant and anti-inflammatory effects. In this study, we aimed to investigate the effects of RML on HIF-1α, VEGF and e-NOS signaling pathway in a rat model of endotoxin-induced uveitis (EIU). Methods: Twenty-eight Wistar albino rats were divided into 4 groups as controls, lypopolysaccharide (LPS) group (5 mg/kg i.p.), LPS  +  RML group (5 mg/kg i.p and 8 mg/kg orally, respectively) and RML group (8 mg/kg orally). EIU was induced by a single intraperitoneal LPS injection. Histopathological and genetical analyses were performed. Results: In histopathological analysis, LPS caused mild anterior uveitis characterized by increased surface area of iris leaflets and ciliary body due to edema, mild to moderate congestion, and inflammatory infiltrate 6 h following the injection. The pathological findings were reduced by RML. Higher inflammation levels seen in LPS group were significantly reduced in LPS  +  RML group. Also, HIF-1 α, eNOS and VEGF expressions increased in LPS and decreased in LPS  +  RML group. Conclusion: RML treatment reversed the changes in the HIF-1α /eNOS/ VEGF signaling pathway in LPS-induced uveitis in rats, preventing the progression of the damage and showed positive effects.